2011
DOI: 10.1161/strokeaha.111.620948
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Efficacy of Circulating Costimulatory Cells After Focal Cerebral Ischemia

Abstract: Background and Purpose-Cerebral ischemia is ensued by a cellular immune depression syndrome. The postischemic functional capacity of T lymphocytes is controversial, and interactions between leukocyte subsets are largely unknown. Understanding the immunologic interplay between antigen-presenting cells and lymphocytes as well as between distinct lymphocyte subsets after stroke might be of clinical/therapeutic significance because animal data argue for a cerebroprotective effect of, for example, CD4ϩCD25ϩ regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 28 publications
1
30
0
3
Order By: Relevance
“…However, these studies also indicated a role for the original brain DCs in post-ischemic neuroinflammation. A significant decrease in circulating DC precursors (Yilmaz and Granger, 2010) after human or experimental stroke has been reported, likely reflecting the reduced co-stimulatory efficacy of circulating cells (Hug et al, 2011). These results suggest that peripheral DCs are recruited from the blood into the ischemic brain, possibly acting either to trigger post-ischemic cerebral immune reactions or inducing systemic immunosuppression.…”
Section: The Impact Of Immune Cells On Stroke Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies also indicated a role for the original brain DCs in post-ischemic neuroinflammation. A significant decrease in circulating DC precursors (Yilmaz and Granger, 2010) after human or experimental stroke has been reported, likely reflecting the reduced co-stimulatory efficacy of circulating cells (Hug et al, 2011). These results suggest that peripheral DCs are recruited from the blood into the ischemic brain, possibly acting either to trigger post-ischemic cerebral immune reactions or inducing systemic immunosuppression.…”
Section: The Impact Of Immune Cells On Stroke Pathogenesismentioning
confidence: 99%
“…With regard to cell function, it was recently reported that the suppressive effect of Tregs was unaltered after stroke in mice and humans (Hug et al, 2011). Thus, an increase in the number of Tregs, rather than an enhancement of the function of each cell, may be responsible for endogenous immunosuppression after stroke.…”
Section: The Impact Of Immune Cells On Stroke Pathogenesismentioning
confidence: 99%
“…Some research has shown that regulatory T (Treg) cells, interleukin (IL)-4, IL-10, and transforming growth factor (TGF)-β contribute to the process of immunodepression [911]. Moreover, TGF-β and IL-10 are essential for the differentiation of Treg cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, also antigen-presenting cells (APCs) in peripheral blood should give important insight on immune response to stroke and the mechanism of tolerance [193]. During cerebral focal ischemia a reduced peripheral costimulatory activity has been observed [194]. Stroke generates imbalance in the acquired immune response and a decrease in circulating dendritic cells [195].…”
Section: Cellular Biomarkers and Immunity Of Strokementioning
confidence: 99%